Ethnic Identity And Consumption Of Popular Culture Among Young Naga People, India - Ota, Satoshi (Penerbit Universiti Sains Malaysia (USM Press), 2011)
The rapid economic growth of India has been internationally well recognised for the past decade. Following the economic growth, its media products are also beginning to be recognised. Hindi media products are most pervasively spread in the country. This research is to investigate how the ethnic minority group of the Nagas from the Northeast India is reacting when they are exposed to Hindi mass culture. By looking at the young Naga people's consumption pattern of media products, the reflection of political status of the Naga in India as well as their identity vis-à-vis India becomes visible. The article argues that Naga people's separate identity from India is reflected in their consumption pattern of media products, which prefer to consume Western media products instead of Hindi mass culture.